Wavelet Analysis and Radial Basis Function Neural Network Based Stability Status Prediction Scheme - Frimpong, Emmanuel Asuming; Okyere, Philip Yaw; Asumadu, Johnson (JURNAL NASIONAL TEKNIK ELEKTRO, 2018)
This paper presents a technique for predicting the transient stability status of a power system. Bus voltages of system generators are used as input parameter. The bus voltages are processed using wavelet transform. Daubechies 8 mother wavelet is employed to extract wavelet entropy of detail 1 coefficients. The sum of wavelet entropies is used as input to a trained radial basis function neural network which predicts the transient stability status. The IEEE 39-bus test system was used to validate the effectiveness and applicability of the technique. The technique is simple to apply and can be implemented in real-time. The prediction accuracy was found to be 86.5% for 200 test cases.Â Keywords : Radial basis function, Transient analysis and Wavelet transform